Lipid profiling and analytical discrimination of seven cereals using high temperature gas chromatography coupled to high resolution quadrupole time-of-flight mass spectrometry. (1st June 2019) - Hammann, Simon; Korf, Ansgar; Bull, Ian D.; Hayen, Heiko; Cramp, Lucy J.E.
Highlights: Cereal lipids were analysed using GC/Q-TOF MS. Differences in sterol, tocopherol and alkylresorcinol patterns could be observed. Novel tocomonoenols and methyl-alkylresorcinols were detected. The cereals could be discriminated by PCA based on non-targeted lipid profiles. Non-targeted lipid profiling could be a new tool for cereal authenticity. Abstract: Minor lipids in cereals (such as phytosterols and alkylresorcinols) can be important for human nutrition and/or be used as biomarkers for cereal intake. However, the analysis of cereal lipids is very challenging due to the complex lipidome comprising several hundred individual compounds present over a wide range of concentrations. Here we present a method for the profiling of cereal lipids using high temperature gas chromatography coupled to high resolution mass spectrometry (GC/Q-TOF MS). The method was used to investigate the lipid profiles of 77 samples of bread wheat, spelt, einkorn, emmer, barley, rye and oats. Distinct differences in the patterns of alkylresorcinols, free and conjugated sterols and tocopherols between the cereals could be observed. Furthermore, traces of tocomonoenols and diunsaturated and methyl-alkylresorcinols (not previously reported in cereals) could be detected. Finally, the lipid patterns in the cereals could be used to separate the cereals by Principal Component Analysis.